Odpowiedź :
Odpowiedź:
zad2
a)[tex]\frac{3}{x+5} +\frac{4}{x-3} =\frac{3(x-3)}{(x+5)(x-3)} +\frac{4(x+5)}{(x+5)(x-3)}=\frac{3x-9+4x+20}{(x+5)(x-3)} =\frac{7x+21}{(x+5)(x-3)}[/tex]
zał:x+5≠0 i x-3≠0
x≠-5 x≠3 D:x∈R-{-5;3}
b)[tex]\frac{7}{x+5}-\frac{3}{x} =\frac{7x}{(x+5)*x} -\frac{3(x+5)}{x(x+5)} =\frac{7x-3x-15}{x(x+5)} =\frac{4x-15}{x(x+5)}[/tex]
zał x+5≠0 lub x≠0
x≠-5 lub x≠0 x∈R-{-5;0}
c)[tex]\frac{x-2}{x+1} *\frac{x^3+x^2}{x^2-4} =\frac{x-2}{x+1} *\frac{x^2(x+1)}{(x-2)(x+2)} =\frac{x^2}{x+2}[/tex]
zał x+1≠0 lub x²-4≠0
x≠-1 lub x²≠4
x≠-2 lub x≠2 x∈R-{-2;-1;2}
d)[tex]\frac{x^2+4x+4}{x-1} :\frac{x+2}{x^2-1} =\frac{(x+2)^2}{x-1} *\frac{(x-1)(x+1)}{x+2} =\frac{x+2}{x+1}[/tex]
zał: x-1≠0 lub x²-1≠0 lub x+2≠0
x≠1 lub x≠-1 lub x≠1 lub x≠-2 x∈R-{-2;-1;1}
zad3
a)[tex]\frac{5x+4}{2x-1} =3[/tex] mnozymy * (2x-1)
zał 2x-1≠0
2x≠1 ⇔ x≠1/2 x∈R-{1/2}
5x+4=3(2x-1)
5x+4=6x-3
5x-6x=-3-4
-x=-7 /:(-1)
x=7
Szczegółowe wyjaśnienie: